The Role of MRI in the Follow-up of Women Undergoing Breast-conserving Therapy. (June 2016) - Shah, Chirag; Ahlawat, Stuti; Khan, Atif; Tendulkar, Rahul D.; Wazer, David E.; Shah, Shilpi S.; Vicini, Frank
Abstract : Objectives: Breast-conserving therapy (BCT) represents a standard of care in the management of breast cancer. However, unlike mastectomy, women treated with BCT require follow-up imaging of the treated breast as well as the contralateral breast as part of posttreatment surveillance. Traditionally, surveillance has consisted of clinical exams and mammograms. However, magnetic resonance imaging (MRI) has emerged as a breast imaging technique utilized as part of high-risk screening programs as well as part of the initial diagnosis and workup of women considered for BCT. At this time, the role of MRI as part of follow-up for women treated with BCT remains unclear. Methods: A systematic review was performed to evaluate the role of MRI following BCT. Results: Although there is no randomized evidence supporting the routine use of MRI in surveillance post-BCT, a review of the literature demonstrates that MRI (1) has increased sensitivity as compared with mammography to detect recurrences, and (2) can help evaluate mammographic abnormalities before biopsy and/or surgery. Conclusions: In patients with higher risk of local recurrence, surveillance with MRI may represent an effective surveillance strategy though subgroups benefiting have not been identified nor has the impact on quality of life and cost been evaluated.